Validation of the Geriatric Oral Health Assessment Index (GOHAI) in the Malay Language - Wan-Nasir W. Othman, DDS, MPHEd, DPH, DipDH; Khairiyah A. Muttalib, BDS, DPHDent; (Blackwell Synergy, 2006)
To translate and validate the Geriatric Oral Health Assessment Index (GOHAI into the Malay language for use in Malaysia.